2012
DOI: 10.1039/c2ra20187a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of poly(ethylene glycol) methacrylate coated CuInS2/ZnS quantum dots and their use in cell staining

Abstract: A simple synthesis of poly(ethylene glycol) methacrylate (PEGMA) coated CuInS 2 /ZnS quantum dots (QDs) has been developed. X-ray diffraction, transmission electron microscopy, and atomic force microscopy observations demonstrated that uniform CuInS 2 /ZnS QDs were successfully prepared. Fourier transform infrared spectroscopy indicated no new peak after the coating process, indicating that only physical interactions occurred during coating and that PEGMA did not disturb the crystal structure of the CuInS 2 /Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…In the FTIR spectrum of CdSe/ZnS QDs (Additional file 1: Figure S1b), the peak at 1,183 cm -1 is the characteristic symmetric and asymmetric stretching vibrations from TOPO ( v P=O ) [37,41]. After transferring from the hydrophobic phase to the hydrophilic phase, for PQDs (Additional file 1: Figure S1c), many peaks emerged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FTIR spectrum of CdSe/ZnS QDs (Additional file 1: Figure S1b), the peak at 1,183 cm -1 is the characteristic symmetric and asymmetric stretching vibrations from TOPO ( v P=O ) [37,41]. After transferring from the hydrophobic phase to the hydrophilic phase, for PQDs (Additional file 1: Figure S1c), many peaks emerged.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of the primary CdSe, CdSe/ZnS, and PQDs shows that (Additional file 1 : Figure S1, details of FTIR) the peak of CdSe at 2,760 ~ 2,930 cm -1 is the characteristic symmetric and asymmetric methylene stretching ( v C-H) that comes from the cosolvent material used in synthesis [ 40 ] (Additional file 1 : Figure S1a). In the FTIR spectrum of CdSe/ZnS QDs (Additional file 1 : Figure S1b), the peak at 1,183 cm -1 is the characteristic symmetric and asymmetric stretching vibrations from TOPO ( v P=O ) [ 37 , 41 ]. After transferring from the hydrophobic phase to the hydrophilic phase, for PQDs (Additional file 1 : Figure S1c), many peaks emerged.…”
Section: Resultsmentioning
confidence: 99%
“…Among these semiconductors, AgInS 2 has a relatively wider 2 band gap ranging from 1.87 eV to 2.03 eV, depending on its crystal structure [12][13][14][15]. For instance, ternary I-III-VI 2 semiconductor materials, such as AgInS 2 , CuInS 2 and Cu(InxGa1-x)Se 2 etc, have been widely investigated for their potential applications in photovoltaic solar cells, light emitting diodes, non-linear optical devices, photocatalytic H 2 evolution under visible light irradiation [14][15][16][17][18]. Most importantly, AgInZnS hollow structure has potential applications in photocatalystic because of its large surface area.…”
Section: Introductionmentioning
confidence: 99%
“…From the XRD patterns shown in Fig. 3a, it can be observed that the characteristic diffraction peaks matched well with the tetragonal chalcopyrite crystal structure of ZAIS (JCPDS 85-1575) 24 and the hexagonal phase of NaYF4:Yb,Er (JCPDS 28-1192), 25,26 the XRD pattern of the UCNP/ZAIS NCs displays nearly the same pattern as pure UCNPs with a tiny diffraction peak at 2q ¼ 28 , which can be indexed to the (112) plane of ZAIS, suggesting the coexistence of ZAIS and NaYF 4 :Yb,Er NPs in the NCs. The successful attachment of QDs to the surface of UCNPs can be established through FTIR spectra and the specic recognition of carboxyl-modied NaYF 4 :Yb,Er NPs before and aer ZAIS coupling (Fig.…”
Section: Resultsmentioning
confidence: 62%